2020
DOI: 10.32598/hdq.6.1.149.2
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Operational First Aid Training Course in Preschool Children

Abstract: Background: All parents of a child know that keeping their child at home is difficult enough, but when the child goes to school, there are new challenges and very dangerous situation. Preparing children for such situations is one of the tasks of the education system. The purpose of this study was to investigate the efficacy of operational first aid training course in preschool children. Methods: This study is a baseline of single-group experiences. The sample size included 150 children who were randomly select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…The findings of this study showed that five-year-old children can learn basic first aid, including calling the ambulance, and managing trauma, head injury, bleeding, nose bleeding, and choking. This finding is in consonance with the earlier studies described in the introduction [ 12 , 15 , 16 ]. Even at 2 and 6 months after the 3-day training program, most of the acquired knowledge of the children in the training was retained and was significantly better than their pre-training level of first aid knowledge and that of the control group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of this study showed that five-year-old children can learn basic first aid, including calling the ambulance, and managing trauma, head injury, bleeding, nose bleeding, and choking. This finding is in consonance with the earlier studies described in the introduction [ 12 , 15 , 16 ]. Even at 2 and 6 months after the 3-day training program, most of the acquired knowledge of the children in the training was retained and was significantly better than their pre-training level of first aid knowledge and that of the control group.…”
Section: Discussionsupporting
confidence: 93%
“…They interviewed 92 children who had undergone ‘ Henry first aid training’ and found that their understanding of first aid had increased post-training. Mohajervatan and colleagues [ 16 ], in an observational study, found that kindergarten children can learn urgent first aid, including calling the ambulance service, handling an unconscious patient, and managing severe bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the research findings show that teaching first aid should begin at a young age [ 20 , 21 , 22 ], several research questions remain unanswered, including the length of time that first aid training knowledge is retained in children’s memories, which instructor is more effective (first aid experts or teachers), when the program should be repeated, and whether the intervention program is actually effective in improving students’ knowledge, skills, and attitudes toward first aid.…”
Section: Discussionmentioning
confidence: 99%
“…Even very young children can learn how to help others in a disaster aftermath. In Iran, for example, children ages five to seven successfully learned lifesaving first aid, including how to control victim bleeding (Mohajervatan et al 2020), and in the Great East Japan Earthquake and tsunami, elementary school students helped with the evacuation of younger children (Pinheiro and Hokugo 2019).…”
Section: Children and Disastersmentioning
confidence: 99%